2021
DOI: 10.1021/acs.jafc.1c02223
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Regulates Cell Growth and Casein Synthesis through the CYTHs/ARFGAP1-Arf1-mTORC1 Pathway in Bovine Mammary Epithelial Cells

Abstract: In the dairy industry, glutamine (Gln) is often used as a feed additive to increase milk yield and quality; however, the molecular regulation underneath needs further clarification. Here, with bovine mammary epithelial cells (BMECs), the effects and mechanisms of Gln on cell growth and casein synthesis were assessed. When Gln was added or depleted from BMECs, both cell growth and β-casein (CSN2) expression were increased or decreased, respectively. Overexpressing or inhibiting the mechanistic target of rapamyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…In vitro, a study has shown that Gln has beneficial effects on cell growth. 28 In the present study, MTT and EdU assays indicated that Gln significantly promoted IPEC-J2 cell proliferation. In addition, TMT proteomics and Western blotting further confirmed that Gln notably upregulated the expression level of cyclin D1, a leading marker of cell proliferation.…”
Section: ■ Discussionsupporting
confidence: 55%
“…In vitro, a study has shown that Gln has beneficial effects on cell growth. 28 In the present study, MTT and EdU assays indicated that Gln significantly promoted IPEC-J2 cell proliferation. In addition, TMT proteomics and Western blotting further confirmed that Gln notably upregulated the expression level of cyclin D1, a leading marker of cell proliferation.…”
Section: ■ Discussionsupporting
confidence: 55%
“…This finding was consistent with those of studies on functional cells, such as bovine mammary epithelial cells (BMECs). 40 Therefore, Arf1 was identified as an important positive regulator involved in Gln sensing by mTORC1 and a promoter of IPEC-J2 cell proliferation. The present study elucidates the role of Arf1 in mediating Gln's effects on mTORC1 activation and IPEC-J2 cell proliferation.…”
Section: ■ Resultsmentioning
confidence: 99%
“…This result suggested that Arf1 was required for Gln-induced mTORC1 activation, which promoted cell proliferation in IPEC-J2 cells. This finding was consistent with those of studies on functional cells, such as bovine mammary epithelial cells (BMECs) . Therefore, Arf1 was identified as an important positive regulator involved in Gln sensing by mTORC1 and a promoter of IPEC-J2 cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…20 In addition, a recent report showed that Arf1, a small GTPase transmitting glutamine signal to mTORC1, can regulate β-casein synthesis through mTORC1 signaling. 21 A previous report revealed that heat stress stimulation promoted the expression of CASTOR1 in the lactating mammary gland of dairy cows. 22 As a crucial upstream regulator of mTORC1, the specific roles of CASTOR1 in heatstress-induced apoptosis are still obscure.…”
Section: ■ Introductionmentioning
confidence: 97%
“…The mTORC1 signaling has a close connection to cellular apoptotic events, and many mTORC1 signaling components, like Akt, AMPK, and GS3Kβ, also exert important roles in regulating apoptosis . In addition, a recent report showed that Arf1, a small GTPase transmitting glutamine signal to mTORC1, can regulate β-casein synthesis through mTORC1 signaling . A previous report revealed that heat stress stimulation promoted the expression of CASTOR1 in the lactating mammary gland of dairy cows .…”
Section: Introductionmentioning
confidence: 99%